Neurological Manifestations in Rheumatoid Arthritis: Scoping Review - Andrianto Selohandono; Ana Budi Rahayu; Dewi Yuniasih (UMSU, 2025)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized primarily by joint inflammation and deformity. Beyond its articular manifestations, RA often presents with significant neurological complications, including peripheral neuropathy, central nervous system (CNS) vasculitis, cervical myelopathy, and cognitive impairments. These manifestations arise from systemic inflammation and autoimmune mechanisms that damage the nervous system, posing serious risks to patient prognosis. Despite their clinical importance, data on the prevalence, pathophysiological mechanisms, and management of these complications remain limited and scattered across studies. This scoping review aimed to synthesize existing literature on neurological manifestations in RA, focusing on their prevalence, underlying mechanisms, and therapeutic approaches.Methods: Using a systematic methodology, relevant studies were identified from databases including PubMed, Scopus, and ProQuest. Articles published between 2020 and 2024 were selected based on specific inclusion and exclusion criteria.Result: The findings reveal that neurological complications in RA range from peripheral neuropathy, affecting up to 50% of patients, to severe conditions like cerebral vasculitis and rheumatoid meningitis. Cognitive impairment, reported in approximately 31% of patients, highlights the long-term burden of the disease. Early diagnosis and tailored therapeutic interventions, such as immunomodulatory therapies, are critical to mitigating these impacts.Conclusion: This review underscores the need for further research to bridge existing knowledge gaps, develop effective diagnostic tools, and improve management strategies for neurological complications in RA. Comprehensive understanding and multidisciplinary approaches are essential for enhancing patient outcomes and quality of life.